Instilling Islamic Religious Education Values in Preventing Bullying Behavior of Students at Tunas Utama Karawang Middle School - Alya Rahma Nabila; Hulailah Istiqlaliyah (Konsultan Jurnal Ilmiah Indonesia, 2024)
The purpose of this study was to describe the efforts of Islamic Religious Education teachers to instill Islamic religious education values ​​in preventing bullying behavior at SMP Tunas Utama Karawang. This study uses a qualitative approach with a descriptive method. Data collection using observation, interview and documentation methods and using data analysis techniques, namely data reduction, data presentation and conclusions. The results of this study indicate that the efforts of Islamic Religious Education teachers to instill Islamic religious education values ​​in preventing bullying behavior at SMP Tunas Utama Karawang are to innovate in learning, find and overcome obstacles in instilling Islamic Religious Education values, and collaborate with other parties. The process of instilling Islamic religious education values ​​in preventing bullying behavior is by providing habits, role models, discipline, advice and conducting open communication. And the results of instilling Islamic religious education values ​​in preventing bullying behavior are reducing bullying actions, instilling values ​​of faith, worship and morals.